PENERAPAN MODEL COOPERATIVE TIPE JIGSAW LEARNING UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATA PELAJARAN FIKIH KELAS XII DI MAN 5 JOMBANG - Alfakhri, Mohamad Wildan (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
The learning method is very important in preparing the learning process activities. Of course, you have to consider choosing strategies and models that are relevant to the learning methods that will be used during the learning process. No exception in class XII Fiqh learning at MAN 5 Jombang. The objectives of this study are to describe: 1) The implementation of cooperative model of jigsaw learning type in class XII jurisprudence subjects at MAN 5 Jombang, 2) The results of implementing cooperative model of jigsaw learning type in improving students' understanding of Fiqh class XII subjects at MAN 5 Jombang, 3) Supporting and inhibiting factors for implementing a cooperative model of jigsaw learning type in improving students' understanding of fiqh subjects in class XII at MAN 5 Jombang. This study uses a qualitative approach and uses a qualitative descriptive type of research to observe directly what is happening in the field and analyze data in the form of sentences or words. Methods of data collection using observation, interviews, and documentation. The results showed that: 1) The implementation of an cooperative model of jigsaw learning type in fiqh class XII subjects at MAN 5 Jombang went well according to the plans made by the teachers and researchers. 2) The results of this implementation are considered effective according to the learning objectives. From the observations and observations of the researchers, the students' understanding was successful in understanding the material and problems given. In addition, students also develop in their courage to speak in front of the class, ask questions, answer, argue and work well with each other among their friends. 3). Supporting factors in its implementation are students' thinking ability, student enthusiasm, student cooperation. While the inhibiting factors are class management and time capacity. Abstrak Metode pembelajaran merupakan hal yang sangat penting dalam mempersiapkan kegiatan proses pembelajaran. Tentunya harus mempertimbangkan untuk memilih strategi dan model yang relevan dengan metode pembelajaran yang akan digunakan selama proses pembelajaran. Tak terkecuali dalam pembelajaran Fikih kelas XII di MAN 5 Jombang. Adapun tujuan penelitian ini adalah untuk mendeskrispsikan : 1) Pelaksanaan model cooperative tipe jigsaw learning pada mata pelajaran Fikih kelas XII di MAN 5 Jombang, 2) Hasil pelaksanaan model cooperative tipe jigsaw learning dalam meningkatkan pemahaman peserta didik pada mata pelajaran Fikih kelas XII di MAN 5 Jombang, 3) Faktor pendukung dan penghambat penerapan model cooperative tipe jigsaw learning dalam meningkatkan pemahaman peserta didik pada mata pelajaran Fikih kelas XII di MAN 5 Jombang. Penelitian ini menggunakan pendekatan kualitatif dan menggunakan jenis penelitian deskriptif kualititatif (field research) untuk mengamati secara langsung yang terjadi di lapangan dan menganalisis data-data berupa kalimat atau kata. Metode pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa : 1) Pelaksanaan model cooperative tipe jigsaw learning pada mata pelajaran Fikih kelas XII di MAN 5 Jombang berjalan dengan baik sesuai dengan perencanaan yang telah dibuat oleh guru dan peneliti. 2) Hasil pelaksanaannya ini terbilang efektif sesuai tujuan pembelajaran. Dari observasi dan pengamatan peneliti, pemahaman peserta didik berhasil dalam memahami materi dan permasalahan yang diberikan. Selain itu, peserta didik juga berkembang dalam keberaniannya untuk berbicara di depan kelas, bertanya, menjawab, berpendapat dan saling bekerja sama dengan baik antar sesama temannya. 3). Faktor pendukung dalam pelaksanaannya adalah kemampuan berfikir peserta didik, semangat peserta didik, kerja sama peserta didik. Sedangkan faktor penghambatnya adalah pengelolaan kelas dan kapasitas waktu.